Mysteries of Mars - De Blasio, Fabio Vittorio (Popular Astronomy,, 2018)
This book introduces the reader to the wonders of Mars, covering all aspects from our past perceptions of the planet through to the latest knowledge on its history, its surface processes such as impact cratering, volcano formation, and glaciation, and its atmosphere and climate. In addition, a series of ten intriguing open issues are considered in a more advanced way. These include such thought-provoking questions as What turned off the planet's magnetic field?, Why are the northern and southern hemispheres so different?, What was the fate of the once abundant water?, and Is there, or was there, life on Mars? Numerous original figures, unavailable elsewhere, reproduce details of images from Viking, CTX, MOC, HiRISE, THEMIS, and HRSC. The book will appeal especially to general readers interested in planetary sciences, astronomy, astrogeology, and space exploration and to students of Earth Sciences and Natural and Environmental Sciences. The higher-level material on the remaining mysteries of Mars will also be of interest to astrogeologists and other researchers.